UPAYA MENINGKATKAN HASIL BELAJAR LEMPARAN DALAM PERMAINAN SOFTBALL MENGGUNAKAN VARIASI PEMBELAJARAN - Arief Rahman; Joko Priono; Imanuddin Siregar (JURNAL TEMATIK, 2022)
This study aims to determine the increase in learning outcomes of throwing in softball games using learning variations using targets. The subjects in this study were students of class VII SMP Kartika I-I Medan, totaling 32 students. The type of research used is classroom action research. To obtain the data in this study, a test of learning outcomes I and a test of learning outcomes II were carried out in the form of the application of basic throwing techniques in a softball game in two meetings. After the data is collected and analyzed, the following results are obtained: (1) In the first cycle after the first learning outcomes test, it can be seen that of the 32 students who were the subjects in this study, it turned out that only 19 students (59.38%) already had complete learning, while the remaining 13 students (40.62%) did not yet have complete learning. The average value obtained only reached 73.34. (2) In the second cycle, it can be seen that 27 students (84.38%) complete the course and already have mastery learning, while the remaining 5 students (15.62%) do not yet have mastery learning. The average value obtained reached 80.09. Based on this, it can be concluded that there is an increase in learning outcomes of throwing in softball games using learning variations using targets in class VII students of SMP Kartika I-I Medan.